Pengaruh Hybrid Work Dan Work Stress Terhadap Job Satisfaction Dengan Mediasi Work Life Balance Dan Job Security Sebagai Variabel Moderasi (Studi Kasus Pegawai Departemen Sumber Daya Manusia di Lembaga XYZ) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
The purpose of this study is to analyze the influence of Hybrid Work and Work Stress on Work Life Balance, analyze the influence of Hybrid Work , Work Stress, and Work Life Balance on Job Satisfaction , analyze the influence of Hybrid Work and Work Stress on Job Satisfaction mediated by Work Life Balance, analyze the analysis of Work Life Balance on Job Satisfaction moderated by Job Security. This study uses a quantitative approach with an explanatory design. The population in this study were all employees of the Human Resources Department of XYZ. The sampling method used was probability sampling, the sampling technique used simple random sampling, the determination of the sample size used SEM provisions of 154 respondents. The data analysis method used Structural Equation Model (SEM) using the Smartpls program version 3.2.9. The results of the study prove that Hybrid Work affects Work Life Balance, Work Stress affects Work Life Balance, Hybrid Work affects Job Satisfaction , Work Stress affects Job Satisfaction , Work Life Balance affects Job Satisfaction , Job Security can moderate the influence of Work Life Balance on Job Satisfaction .